Climate change and tourism in South and Central America - Navarro-Drazich, Diego; Christel, Lucas G.; Gerique-Zipfel, Andres; Grimm, Isabel; Rendón, Maria Luisa; Schlemer Alcântara, Liliane; Abraham, Yasmin; Conde, Maria del Rosario; De Simón, Cecilia (Journal of Sustainable Tourism, 2023)
This paper assesses the state of knowledge of climate change and tourism in South and Central America, with a special focus on the characteristics of the tourism sector, the particularities of climate risks of the region and the sectoral GHG contribution. We conducted a scientific literature review (by region and by country) in Spanish, Portuguese and English using publications in the Scopus and Google databases to the end of 2021. In parallel, we performed a search for institutional publications, programs, and strategies on climate change and tourism in South and Central American countries. This analysis identified the main challenges and potentialities between tourism and climate change in the region. Among the main findings is the limited number of studies and lack of primary data to inform policy formulation and tourism planning. Likewise, national, and regional public policies specific to tourism are scarce, while multisectoral climate plans have only recently been developed and, consequently, are difficult to evaluate.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Central America; climate change; South America; Tourism